(NkARTOGRAFI^ESKOE OBESPE^ENIE NARODNOHOZQJSTWENNOJ PRAKTIKI (B:s [(NsBORNIK STATEJ(B] /s - (NaRVANOW(B, (Ne(B.(Np(B.s; (NbA@RA(B, (Nw(B.(Nn(B.s ((NmOSKWA (B:s (Nmfgo(B,s, 1990)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(Nan sssr(B, (NmOSKOWSKIJ FILIAL gEOGRAFI^ESKOGO OB]ESTWA sssrs
Keywords: (NkARTOGRAFIQs